Gotland ponies on extensive pastures – a welfare assessment - Börjesson, Mathilda (SLU/Dept. of Animal Environment and Health (until 231231), 2015)
Swedish farmers have the possibility to be subsidized by EU rural development programme for grazing animals on pastures to promote the biodiversity of flora and fauna. The environmental remedy sometimes does not allow supplementary feed and at the same time the Swedish Animal Welfare Act and the Swedish Agricultural Board’s regulations for animal welfare and protection states that animals, in this case horses, shall be fed with food of good quality and adapted for the species. The regulations also state that they should have an individual feeding regime that enables them to maintain a normal body condition.